LAÇOS DE COMPADRIO ENTRE ESCRAVIZADOS NO SUL DO MARANHÃO (1854-1888). - ANDRADE, Antônia de Castro (2017)
A study that aims to discuss how black slavery was experienced by the Sertanean society in the south of Maranhão, analyzing, through inventories and records of baptisms, which strategies the enslaved used to create spaces of sociability and solidarity in a medium which was so hostile to him. It is necessary to (re) think the relationships that were born in and out of cattle ranching in the backlands of the south of Maranhão. More than that, it is necessary to construct a narrative that can give visibility and even readability to all the historical agents that composed that social space.